1969
DOI: 10.1159/000230740
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Actions of Different Bronchodilators in Asthma

Abstract: The actions of the following pressurized bronchodilators were compared by administration to 24 asthmatics: (1) Medihaler Iso Forte, (2) Alupent, (3) Medihaler-duo, (4) Bronchilator, and (5) Prenomiser Plus. These contained one or more of the following: isoprenaline, orciprenaline, isoetharine, phenylephrine, atropine methonitrate, and thenyldiamine. The dose was a single discharge from the container. The response was assessed by calculating the mean percentage change in F.E.V. at intervals after inhalation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In again confirming the greater utility of the [R,, x Vtg] calculation (compared with simple recording of R.) in estimating bronchial obstruction, our observations suggest that maximally effective inhalant doses may not be provided by conventional pressurized nebulizers whether given by well-instructed patients (Freedman, Meisner, and Hill, 1968) or by a physician (Ishikawa and Cherniack, 1969). Improvement in airways indices following selfdosage of the isoproterenol with phenylephrine aerosol was of lesser degree than the changes seen when the same mist was given by the physician from the identical apparatus, with the effects of both statistically inferior to those following the use of the breath-actuated device which did not require manual synchronization of mist release with patient inspiration.…”
Section: Discussionsupporting
confidence: 61%
“…In again confirming the greater utility of the [R,, x Vtg] calculation (compared with simple recording of R.) in estimating bronchial obstruction, our observations suggest that maximally effective inhalant doses may not be provided by conventional pressurized nebulizers whether given by well-instructed patients (Freedman, Meisner, and Hill, 1968) or by a physician (Ishikawa and Cherniack, 1969). Improvement in airways indices following selfdosage of the isoproterenol with phenylephrine aerosol was of lesser degree than the changes seen when the same mist was given by the physician from the identical apparatus, with the effects of both statistically inferior to those following the use of the breath-actuated device which did not require manual synchronization of mist release with patient inspiration.…”
Section: Discussionsupporting
confidence: 61%
“…identified 80% with at least minimal and 50% with moderate or greater FEV1 BDR, while the ATS/ERS method identified only 20.6% positive.Interpretation of BDR for obstructive airways disease (OAD) patients in pulmonary laboratories has long been disputed. Nearly fifty years ago, Freedman et al suggested that most physicians would agree that a FEV1 increase <10% is valueless and that a 20%-30% increase was likely useful23 . In 1974, a CHEST advisory committee recommended positive BDR required FEV1 change in both percent and absolute volume24 .…”
mentioning
confidence: 99%
“…Doses of isoprenaline were given at five minute intervals since the response to inhaled isoprenaline is near maximum at this time and a longer time would have rendered earlier doses inactive by the end of the study. 3 The response was greater with the cumulative technique than the non-cumulative technique for FEVy, FVC, and PEFR, though the differences were significant only for FEVy. Since the magnitude of the difference between the two techniques was similar for FEVI, FVC, and PEFR-15%, 9%, and 16% respectively-differences in statistical significance presumably reflect the relatively small differences between the two techniques and the better reproducibility of FEV1 measurements.…”
Section: Discussionmentioning
confidence: 83%